The life history calendar technical aspects of data analysis using contraceptive calendar of the Bangladesh demographic and health survey. - Khatun, Mohsina (2001)
ABSTRACT: The life history calendar is a technique to collect life history data retrospectively. Several researchers have discussed the quality of calendar data as compared to traditional techniques. The analysis of life history calendar data is discouraged because the data structure is not suited for most software packages. The initial procedure of extracting the necessary variables from the calendar has not been documented yet in any detail. In this paper we attempt to fill this gap by extracting episode data from individual-based data. The procedure is illustrated using the contraceptive use calendar of the Bangladesh Demographic and health Survey. SPSS is used throughout and the SPSS syntax is shown. All the steps are described in detail. That should help the reader to change or develop the program according to his or her research question(s). The paper also documents how to prepare episode files for TDA and input files for multistate life table analysis in Excel. Keywords : Life history calendar, Contraceptive use dynamics, Multistate life table, Transition data